Peningkatan Layanan Kesehatan Pemeriksaan Tekanan Darah, Cek GDS Kolesterol dan Senam Diabetic untuk Para Lansia di Desa Loundoun Popayato Provinsi Gorontalo - Hasinuddin, Mutmainnah Hasi; Yanriatuti, Ida; Kantohe, Imelda (Jurnal Abdimas Kesehatan (JAK), 2024)
Health examinations are examinations that focus on primary and secondary prevention by looking holistically at various health factors that can cause certain diseases. One of the factors that causes elderly people to be susceptible to disease is an unhealthy lifestyle. An unhealthy lifestyle leads to diseases, such as gout, hypertension, diabetes mellitus and heart disease. Data from Riskesdas (2018) shows that many elderly people aged 55 to 75 years and above are infected with coronary heart disease. According to data from the World Health Organization (WHO), stroke and heart disease are often caused by high levels of cholesterol in the blood. Based on the results of a survey conducted by fellow Palu Salvation Army STIKES students, many elderly people are affected by diabetes, stroke and gout. This can only happen due to the local people's habit of burning unused waste and plants. The purpose of writing this article is to inform the public, especially the elderly, about the dangers of diseases, such as diabetes, stroke, heart disease, arthritis due to gout, and others. The method used is examination and exercise. The results and discussion obtained were that the majority of elderly people in Loundoun Popayato Village had high blood sugar and cholesterol levels, while uric acid and glucose levels were in the normal rangel.Londoun popayato Village is affected by diabetes,stroke and gout .The elderly population in Loundoun popayato village with an age range of 50-59 is 224 people and in the age range 60-69 is 183 people ,and in the age range 70 there are 87 people . The conclusion is that this shows that on average Loundoun Popayato Village residents have a high risk of diabetes, coronary heart disease, stroke, etc.